Reliable Damping Simulation of Highly Perforated Micro-Electro-Mechanical Systems through Physical Compact Modeling - Friederike Michael; Barbara Leikam; Gabriele Schrag (Proceedings)
We present an approach to estimate damping in highly and irregularly perforated microplates over a wide range of pressures applying physics-based compact models implemented in a flux-conserving finite network. The models are coded in Verilog A, which allows for simulation using a standard circuit simulator. This provides an efficient and customizable way to determine damping beyond the state of the art, and thus, to tailor and design the dynamic operation of MEMS in a predictive manner.